CD25 as an adverse prognostic factor in elderly patients with acute myeloid leukemia. Issue 6 (3rd July 2017) - Fujiwara, Shin-ichiro; Muroi, Kazuo; Yamamoto, Chihiro; Hatano, Kaoru; Okazuka, Kiyoshi; Sato, Kazuya; Oh, Iekuni; Ohmine, Ken; Suzuki, Takahiro; Ozawa, Keiya
ABSTRACT: Objectives: CD25 has been reported to be highly expressed in leukemia stem cells and correlated with adverse outcomes in young patients with acute myeloid leukemia (AML). However, the significance of CD25 expression in elderly patients with AML has not yet been investigated. Methods: We retrospectively analyzed 154 newly diagnosed AML patients aged 60 years or over by flow cytometry. Results: CD25-positive AML was characterized by high white blood cell counts, secondary AML, rare favorable karyotypes, and positivity for CD34 and CD7 antigens, compared with CD25-negative AML. CD25 positivity was significantly correlated with an inferior complete remission (CR), event-free survival (EFS), and overall survival. Multivariate analysis showed CD25 positivity to be a significant prognostic predictor of CR and EFS. A regimen of low-dose cytarabine and aclarubicin combined with granulocyte-colony-stimulating factor (CAG) led to higher CR rates in the CD25-positive AML patients than intensive chemotherapies. CD25 expression was increased at relapse and in the development of leukemic status from myelodysplastic syndrome or myeloproliferative neoplasm. Discussion: An effective treatment strategy for elderly patients with CD25-positive AML has not been established. Further studies are needed to evaluate the effect of a CAG regimen and allogenic stem cell transplantation in patients. Conclusion: CD25 is an independent prognostic factor in elderly AML patients. Alternative therapies for CD25-positive elderly AML patients are needed.